Therapeutic Approaches to Remorse in Sentencing Recommendations: A Qualitative Study of Probation Officers - Berryessa, Colleen M. (Criminal justice and behavior, 2023)
Stemming from interviews with 151 probation officers in the United States, this study produces a qualitative model that illuminates the extent to and ways in which probation officers draw from principles of Therapeutic Jurisprudence to consider remorse as evidence of a client’s potential for rehabilitation (remorse shows “therapeutic guilt” through which an individual being sentenced acknowledges wrongdoings, takes responsibility, and shows behavioral changes) and reconciliation (remorse is a device for “rebalancing power” by shifting responsibility for bad acts away from victims and community, as well as allows the individual being sentenced to seek and receive forgiveness via apologies and “payback”) during sentencing. Correspondingly, the model further suggests how these officers use their therapeutic views of remorse to inform their presentencing recommendations for sentencing plans that prioritize community reintegration. Finally, this article discusses the model’s implications and the potential adoption of Therapeutic Jurisprudence approaches in sentencing.